THE APLICATION OF MULTISENSOR LEARNING ON THEMATIC LEARNING - NAFI'AH, JAMILATUN JAMILATUN (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
Learning materials that are still abstract is one of the obstacles for teachers in understanding students. Specific thematic learning, it is necessary learning that not only keeps students active in learning activities, but also students can understand the intent and purpose of the theme they are learning, the students' understanding can be improved through the model. Multisensory learning. This research is aimed to describe the application of the learning process of Multisensorim to the thematic teaching of the subtheme of the preservation of the natural resources in Indonesiadi class. IV. Madrasah Ibtidaiyah. Mambaul Hidayah Pulorejo Gumukmas academic year 2017-2018.